Analysis and comparison of two methods for the estimation of 3D motion parameters - Gonçalves, Nuno (2003)
This paper analyzes the problem of motion estimation from a sequence of stereo images. Two methods are considered and their differential and discrete approaches are compared. The differential approaches use differential optical flow whereas the discrete approaches use feature correspondences. Both methods are used to compute, first, the 3D velocity in the direction of the optical axis and, next, the complete rigid motion parameters. The uncertainty propagation models for both methods and approaches are derived. These models are analyzed in order to point out the critical variables for the methods. The methods were extensively tested using synthetic images as well as real images and conclusions are drawn from the results. Real images are used without any illumination control of the scene in order to study the behavior of the methods in strongly noisy environments with low resolution depth maps.